Gallium Oxides Photocatalysts Doped With Fe Ions for Discoloration of Rhodamine Under UV and Visible Light - Orozco, S.; Rivero, M.; Montiel, E.; Espino Valencia, J. (Frontiers in Environmental Science, 2022)
Heterogeneous photocatalysis is a highly efficient process for degrading recalcitrant and emerging pollutants. Rhodamine B (RhB) is a nonbiodegradable and highly refractory compound persistent in conventional processes. In this work, we investigate the photocatalytic activity of gallium-based catalysts undoped (GO) and doped with Fe ions (GOFe). Catalysts were synthesized by simple precipitation assisted with an ultrasonic transducer and subjected to thermal treatment at different temperatures (500, 650, 800 and 950 °C). They were characterized by thermogravimetric analysis (TGA), Fourier transform infrared (ATR-FTIR) spectroscopy, and X-ray diffraction (XRD). Catalysts were tested in the discoloration of Rhodamine B dye. Experiments were carried out at different pH values (3.00, 5.00 and 9.00) in the presence of H2O2 and using Visible and Visible-UV light sources as study variables. Better discoloration results were observed for GO and GOFe under acid environments (pH = 3.00) for both light sources. GO and GOFe photocatalyst showed high effectiveness in the discoloration of RhB completing the process in 300 min, under a Visible-UV lamp at pH = 3.00. Incorporating Fe ions into the gallium oxides matrix decreases its bandgap, allowing it to activate under visible light. The discoloration process exhibited pseudo-zero-order apparent kinetics.